Komunikasi Perempuan dalam Keluarga Berpoligami di Madura - Nikmah Suryandari; Roos Yuliastina (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
The phenomenon of polygamy has become a polemic in eastern countries, such as Indonesia. As a Muslim country, Indonesia recognizes two systems in families, namely the system of monogamy and polygamy Marriage in Madura is not much different from the traditional marriage system in other regions. The practice of polygamy was initially only carried out by Madurese men who had positions or had more material, such as religious leaders, officials, or blater. However, this practice of polygamy is currently being carried out by Madurese men who are not material enough. Based on this, the practice of polygamy from Madura can be likened to an iceberg phenomenon. The problem in this research is how is the communication of women in polygamous families in Madura? This study uses a constructivist paradigm with descriptive qualitative research. This data collection uses in-depth interviews, observations. This study uses a constructivist paradigm with descriptive qualitative research. This data collection uses depth interviews, observations. Informants in this study were women in polygamous marriages, both first and second wives. The supporting informants were husbands in polygamous families and polygamous female family. The results of this study indicate that in the communication of women in polygamous families in Bangkalan, using contradictory messages in conveying messages, especially first wives to second wives. Communication of women in polygamous families also involves verbal and nonverbal communication among the participants. Communication of women in polygamous families also has the potential to cause conflict.